Effect of banana blossom vegetables for speed up recovery of perineal wounds - Layla Imroatu Zulaikha; Emi Yunita; Qurratul A'yun (Alma Ata University Press, 2022)
Background: The process of delivery through the birth canal has a risk of experiencing perineal tears, perineal tears can occur spontaneously or tear through episiotomy. The presence of perineal wounds can be one of the predisposing factors for infection during the puerperium. Based on the Indonesian Health Profile in 2018, post-partum wounds are still a common cause of infection, reaching 80-90%. Complementary therapy is the right solution to overcome health problems. One type of biodiversity that can be used as herbal therapy to speed up recovery process of perineal wounds is banana blossom which contains iron which is needed for hydroxylation of proline, lysine, vitamins, flavonoids, and proteins. antioxidant effect which is indispensable in the wound healing processObjectives: This study aims to determine the effectiveness of consuming banana flower vegetables to accelerate perineal wound healing.Methods: This research is a quasi-experimental study with a Posttest Only Control Group design and then analyzed using a non-parametric test, namely the Mann Whitney test and a significance level of 0.05, to see the difference in perineal wound healing time between the control group and the experimental groupResults: Based on the results of statistical tests using the Mann Whitney U-Test, a p value of 0.000 <0.05 (α) was obtained which indicated that H1 was accepted and H0 was rejected, meaning that there was a difference in the duration of perineal wound healing between respondents who consumed banana flower vegetables and respondents who did not consume banana heartConclusions: Banana flower has a high antioxidant content which makes the process of joining the tissues on both sides of the wound due to tearing to take place more quickly. With the results of this study, it is hoped that all postpartum women who experience perineal tears can continue to consume banana flower vegetables until the perineal wound heals.